Adolescentes em conflito com a lei: memórias e trajetórias de vivências na escola - MONTEIRO, Regina Fernandes (Universidade Federal do Pará, 2012)
This study aims to uncover the memory of school adolescents in conflict with the law and measures that meet the Foundation for Children and Adolescents of Pará in Internment Unit Socio-Val-de-Dogs. The intention is to trace through the discursive statements of these subjects, their inroads into the educational environment and thereby identify what made them leave school early and / or submit their curricula in a high rate of repetition. The questions guiding this study are: What factors contributed to these teens leave the educational environment so early? To what extent the school and social exclusion were factors relevant to the involvement of adolescents with violence and crime? How committed to the training of school adolescents in conflict with the law, taking into account the school's role in the formation of the subject? Using the guiding questions that the study is to identify network Meanings are involved in these questions. The sample included the participation of 18 adolescents aged 12-17 years old in high school first grade of primary education up to 8th grade of elementary school, born in Para State, fulfilling socio-educational measures for the infraction that will damage to public property (Art. 163) the robbery followed by death (Art.121 / c Art. 14). Was used as instruments to collect data to semi-structured interviews and documents donated by the Foundation, as the records with personal data and monitoring of each teen. The corpus of research has been analyzed by the following issues-issues: School, Family, Violence and Crime, Interpersonal Relations and Future Prospects. The theoretical basis for data analysis follows the design of Bakhtin on the network of meanings and authors that discuss aspects related to the themes. Used for such authors as ROSSETTI and Ferreira (2004); ARROYO (1997); BOSSA (2002); CORDIO (1996) and Vygotsky (2000); PINTO (2002), among others. In this perspective, the goal was to find correspondence with the principles and criteria that could contribute to the foundation of this analysis, promoting interaction between different forms of knowledge production, especially from the data presented to the process of schooling of these subjects, once that contributed to failures, school failures, gaps, and often for truancy.